Heart Failure Self-care Within the Context of Patient and Informal Caregiver Dyadic Engagement: A Mixed Methods Study. Issue 4 (July 2018) - Buck, Harleah G.; Hupcey, Judith; Wang, Hsiao-Lan; Fradley, Michael; Donovan, Kristine A.; Watach, Alexa
Abstract : Background: Recent heart failure (HF) patient and informal caregiver (eg, dyadic) studies have either examined self-care from a qualitative or quantitative perspective. To date, the 2 types of data have not been integrated. Objective: The aim of this study was to understand HF self-care within the context of dyadic engagement. Methods: This was a cross-sectional, mixed methods (quantitative/qualitative) study. Heart failure self-care was measured with the Self-care of Heart Failure Index (v.6) dichotomized to adequate (≥70) or inadequate (<69). Dyadic symptom management type was assessed with the Dyadic Symptom Management Type scale. Interviews regarding self-care were conducted with both dyad members present. Content analytic techniques were used. Data were integrated using an information matrix and triangulated using Creswell and Plano Clark's methods. Results: Of the 27 dyads, HF participants were 56% men, with a mean age of 77 years. Caregivers were 74% women, with a mean age of 66 years, representing spouses (n = 14) and adult children (n = 7). Quantitatively, few dyads scored as adequate (≥70) in self-care; the qualitative data described the impact of adequacy on the dyads' behavior. Dyads who scored higher, individually or both, on self-care self-efficacy and self-care management were less likely to change from their life course pattern. Either the patient or dyad continued to handle all self-care as they always had, rather than trying new strategies or reaching out for help as the patient's condition deteriorated. Conclusions: Our data suggest links that should be explored between dyadic adequacy and response to patients' symptoms. Future studies should assess dyadic adequacy longitudinally and examine its relationship to event-free survival and health services cost.